MALE AND FEMALE PERCEPTION OF TABOO IN ACEH LANGUAGE - Maria Ulfa; Mulyadi Mulyadi; Mhd Pujiono; Khairina Nasution (Universitas Islam Sumatera Utara, 2022)
This research is to obtain male and female perspectives on taboo language. This study used qualitative research with a phenomenology approach. There are fourteen subjects in this research that consist of seven males and seven females, the age of the subject is categorized into a start from early adulthood to middle adulthood. The researchers used observation and gave questionnaires to find the data. The result of this research showed that; 1) males and females ever use taboo language, but a male dominantly used taboo language, about 57%, compared to females 14% in using taboo language in daily communication. 2.) A taboo language used by an adult is very limited; adults only know about the taboo related to dirty words and insults, showing that taboo language understood by an adult is shifting in believing and practicing. 3) Male and Females have the same perspective towards taboo language, Most females believe that taboo is impolite words.